(untitled) (REMUNOM, 2025)
Combined oral contraceptives (COCs) are widely recognized as one of the most effective and widely used reversible contraceptive methods worldwide. The cardiovascular risk associated with the use of COCs is even more significant in women who have additional risk factors, such as smoking, high blood pressure, obesity, and migraine. These factors, when combined with the use of hormonal contraceptives, amplify the risk of serious adverse events. To discuss the relationship between the use of oral contraceptives and the risks of stroke and acute myocardial infarction (AMI) in women. This study is an integrative review of the literature. To answer the guiding question, a systematic search was carried out in scientific databases that included studies related to the topic. The databases chosen for the research were the Latin American and Caribbean Literature in Health Sciences (LILACS) and the Medical Literature Analysis and Retrieval System Online (MEDLINE) and Pubmed. The search criteria involved the use of descriptors in Portuguese, combined with the Boolean operator AND to refine the results. After an exploratory analysis of readings and the applicability of the predetermined inclusion criteria, this research consisted of 08 scientific articles that accepted and contemplated the theme in question, as well as the previously established criteria. Hormonal contraceptives are among the most efficient reversible contraceptive methods available and used worldwide. Although estrogen is attributed to the risk of venous thromboembolism due to its frequent use, it has beneficial outcomes in reducing the risk of ovarian and endometrial cancer. Therefore, it is clear that hormonal contraceptives interfere with the homeostasis of the cardiovascular system and, therefore, the importance of an investigation prior to prescribing a hormonal contraceptive for the patient, which takes into account her individual cardiovascular risks, such as age, presence of comorbidities, smoking and family history.